Acute effects of polyphenols from cranberries and grape seeds on endothelial function and performance in elite athletes - Labonte, K.; Couillard, C.; Motard-Belanger,A.; Paradis, M.-E.; Couture, P.; Lamarche, B. (Sports, 2013)
We examined how intake of polyphenols modifies brachial artery flow-mediated dilation (FMD) at rest, and cycling anaerobic performance, in elite athletes. In the first randomized cross-over study, FMD was measured over a three-hour period on two occasions in eight elite male and female athletes after acute consumption of either polyphenols from cranberries and grape seeds (600 mg) or a polyphenol-free placebo drink. Consumption of the polyphenol-rich drink led to a significant increase in FMD compared to placebo (p = 0.02), with a peak at 60 min. In a second study, 12 elite male and female athletes completed a three-kilometer time trial (TT) on an ergocycle on two occasions in random order, either after consumption of 800 mg of polyphenols or a placebo. Acute intake of the polyphenol extract had no impact on the three-kilometer time trial completion. However, plasma lactate levels were significantly lower before and after the TT when subjects consumed the polyphenols vs. placebo (p < 0.05). Results suggest that polyphenols from cranberries and grape seeds acutely modifies FMD at rest in elite athletes but this does not translate into enhanced cycling anaerobic performance.